2005
DOI: 10.1093/afraf/adi015
|View full text |Cite
|
Sign up to set email alerts
|

Diaspora and drug trafficking in West Africa: A case study of Ghana

Abstract: This article interrogates the emergence of drug trafficking in contemporary Ghana and West Africa within the context of a global political economy, situated within a deeper historical perspective. It examines the earlier trafficking of cannabis along the coast of West Africa in the colonial period, and the later transnational networks that have emerged to promote international drug trafficking (cocaine and heroin). The article probes how the African diaspora and international travel service these emerging drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 11 publications
4
40
0
2
Order By: Relevance
“…As is the case with legal trade, paired countries with intense migration flows are also more likely to traffic heroin with each other. This confirms findings from previous studies on the influence of migration patterns on drug trafficking routes (Akyeampong, 2005;Paoli & Reuter, 2008;Zaitch, 2002). For instance, Paoli and Reuter (2008) found that Turkish and Albanian ethnic groups dominate the import and retail distribution of heroin in Europe.…”
supporting
confidence: 92%
“…As is the case with legal trade, paired countries with intense migration flows are also more likely to traffic heroin with each other. This confirms findings from previous studies on the influence of migration patterns on drug trafficking routes (Akyeampong, 2005;Paoli & Reuter, 2008;Zaitch, 2002). For instance, Paoli and Reuter (2008) found that Turkish and Albanian ethnic groups dominate the import and retail distribution of heroin in Europe.…”
supporting
confidence: 92%
“…West Africa was a transit site for heroin trafficking as early as the 1950s, when Lebanese smuggled Near East heroin from Beirut through Kano, Nigeria and Accra, Ghana, to New York City (Akyeampong 2005;Ellis 2009). Nigerians and Ghanaian traffickers joined the global movement of illicit substances during the 1960s when they began exporting cannabis to Europe.…”
Section: Drug Trafficking In Africamentioning
confidence: 99%
“…The paper looks at how drug trafficking had been an issue since the colonial times and how the whole process has been internationalized especially through the borders of Ghana and other West African nations such as Nigeria. One can say that it is through the internationalization of drugs as Emmanuel Akyeampong posits that some Nigerians coming to the East now see Malaysia and Indonesia as a soft target for their drug peddling activities hence the problem which these nations also face presently and which forms one of the issues in our paper (Akyeampong, 2005). This paper is divided into six parts, beginning with the introduction.…”
Section: Introductionmentioning
confidence: 97%